2005
DOI: 10.1093/jac/dki163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inoculum size of Staphylococcus aureus and Pseudomonas aeruginosa on in vitro activities and in vivo efficacy of fluoroquinolones and carbapenems

Abstract: Our results suggest that decreased bactericidal activity, or the in vitro PAE of carbapenems and fluoroquinolones, is related to the reduced in vivo protective effect against infection caused by high inoculum with S. aureus or P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
47
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 20 publications
8
47
1
2
Order By: Relevance
“…Since there was no washout of signal molecules or other substances, a time-kill experiment as in our study may overestimate the inoculum effect in vivo. However, several animal infection model studies showed the significance of the inoculum effect in vivo (25,38,47,60). It is important to note that the clinical relevance of the inoculum effect has rarely been demonstrated, and numerous factors, such as host defense and severity of infection, greatly influence antimicrobial effect and treatment success in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since there was no washout of signal molecules or other substances, a time-kill experiment as in our study may overestimate the inoculum effect in vivo. However, several animal infection model studies showed the significance of the inoculum effect in vivo (25,38,47,60). It is important to note that the clinical relevance of the inoculum effect has rarely been demonstrated, and numerous factors, such as host defense and severity of infection, greatly influence antimicrobial effect and treatment success in patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, PKPD target values may vary between antibiotics and pathogens (2, 3) and may not be universal for all infections (27) and types of outcomes (44,59). For example, severe infections, such as endocarditis, infections of prostheses, and ventilator-associated pneumonia are known to have a high density of bacteria, which is associated with a higher mortality (25,47,54,60). Furthermore, an increased density of bacteria represents a greater challenge to the immune system and may result in higher bacterial toxin concentrations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some other studies have shown that the in vitro efficacy of antimicrobials can depend on the size of the bacterial inoculum, with drugs being more potent against low than against high inocula (10)(11)(12). It was subsequently shown in vivo that lower antibiotic doses given in the early prepatent phase of an infection, when the pathogen burden was still low, were as effective as higher doses administered during the patent phase of infection, as characterized by overt clinical symptoms and a high bacterial burden (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…45 These results showed that the knowledge of the influence of inoculum is useful for further research, namely to assess bacterial adhesion to other biomaterials. 46,47 The biofilm structure and morphology formed on these biomaterial surfaces, over time, were also assessed by SEM. A mature biofilm with EPS production and three-dimensional mushroom-like or pillar-like structures was observed, on both biomaterial surfaces.…”
mentioning
confidence: 99%